Analysis of Student Scientific Communication Based on The Development and Use of Diorama Media Using The Guided Inquiry Model - Sho'idah, Yunis; Septaria, Kiki; Wulandari, Siska Ayu (Universitas Islam Lamongan, 2025)
Considering 7th grade science teachers only employ media pictures from textbooks, there is a need to produce three-dimensional diorma media. The creation of diorama media is also an endeavor to strengthen students' scientific communication skills. The study's objectives were as follows: 1) to investigate the validity of diorama media, 2) to investigate the practicability of diorama media, and 3) to investigate the influence of guided inquiry-based diorama media on scientific communication of students using pre-test and post-test test instruments. The research model utilized is research and development, which creates goods utilizing the ADDIE research paradigm. The ADDIE development approach has five steps: analysis, design, development, implementation, and evaluation. Techniques for gathering information based on the instruments used, particularly observation, questionnaires, and cognitive tests, were carried out on two classes, namely the control class learning using the lecture method and the experimental class learning using three-dimensional diorama media, and the results were analyzed. The analysis revealed that the diorama media's validity was 89.9%, its practicality was 86%, and there was a significant difference between the basic pre-test and post-test with a Sig (2-tailed) value of 0.000 < 0.05. According to the study's findings, diorama media is legitimate and useful in learning content on the interaction of living things, and it has an impact on students' scientific communication.